Teacher Performance Management in Madrasa - Irawan, Irawan; Yetri, Yetri; Amiruddin, Amiruddin (Journal of Advanced Islamic Educational Management, 2023)
Teachers in madrasas have a central role in realizing educational goals. Teacher performance affects students' academic achievement and shapes their attitudes, values, and moral character. Managing teacher performance in madrasah has its challenges, including fulfilling training and professional development needs, objective performance appraisal, appropriate motivation and rewards, and efficient resource management. This study aims to analyze teacher performance management at MTs Negeri 1 Lampung Utara. The research method used is qualitative. Data collection techniques were interviews, observation, and documentation. The research subjects were the madrasah head and teachers. The results showed that teacher performance management is carried out in four aspects, namely planning, organizing, implementing, and supervising. Based on the research data, it was found that planning and supervision were effective. However, in terms of implementation, several problems were found, namely external and internal problems. To overcome these problems, several things are applied, namely, developing several characteristics in planning, organizing personnel, implementing programs, providing intensive supervision, instilling Islamic values and brotherhood, and optimizing the functions and roles of teachers.